Sugarcane Growing and the Livehoods of Small-Scale Farmers in Jinja District, Uganda - Muhamud Wambede Nabalegwa; Robert Tweheyo; Joyfred Asaba; Muhamed Waibi (Forum Geografi, 2022)
This study focused on establishing the relationship between sugarcane growing and the livelihood of small-scale farmers in Jinja District.  It was guided by three objectives namely: to characterize individual farmers and their farms, establish benefits from sugarcane farming to the farmer’s livelihoods and find out the effect of sugarcane growing on household food security in the area. The study adopted descriptive research design. The target population of this study were sugarcane growing households’ heads and Village Chairpersons of sugarcane out-growers association.  The study employed the purposive and simple random sampling techniques. A sample size of 42 respondents from a population of 362 small-scale farmers.  The methods of data collection included; use of questionnaires, interviewing, focus group discussions and observation.  The study generated both qualitative and quantitative data. The data collected was analysed by computing percentages while qualitative data was analysed by coding and establishing common themes. The study findings revealed that although women are fully involved in sugarcane growing, ownership of farms is dominated by men. The dominant age group among the sugarcane farmers is between 30 to 60 years, with mainly primary education graduates. The average farm size was 3 acres and the larges part of the farm land is devoted to sugarcane growing. There are some positive benefits from sugar growing, though many challenges have been identified. Most smallholder farmers are experiencing food insecurity.  Based on the findings of the study it was recommended that there was need to encourage people owning land less than five acres to practice mixed farming, use scientific methods of farming such as intercropping, crop rotation, use fertilizers to facilitate better yields and crop diversification to improve both on their earnings and food security.